2010
DOI: 10.1186/1758-5996-2-30
|View full text |Cite
|
Sign up to set email alerts
|

Association between insulin resistance and c-reactive protein among Peruvian adults

Abstract: ObjectiveInsulin resistance (IR), a reduced physiological response of peripheral tissues to the action of insulin, is one of the major causes of type 2 diabetes. We sought to evaluate the relationship between serum C-reactive protein (CRP), a marker of systemic inflammation, and prevalence of IR among Peruvian adults.MethodsThis population based study of 1,525 individuals (569 men and 956 women; mean age 39 years old) was conducted among residents in Lima and Callao, Peru. Fasting plasma glucose, insulin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
44
1
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 24 publications
6
44
1
9
Order By: Relevance
“…6,22 Moreover, experimental and epidemiological data have indicated that the inflammatory process is associated with impaired insulin sensitivity and the development of dysglycemic conditions. 30 A study conducted in Peru among 1525 individuals 31 found that elevated CRP were significantly and positively associated with increased mean fasting insulin concentrations and mean HOMA-IR (Po0.001) in both women and men. Women with CRP concentrations 42.53 mg l À1 (upper tertile) had a 2.18-fold increased risk of IR (OR¼2.18; 95% CI 1.51-3.16) compared with those in the lowest tertile (o0.81 mg l À1 ).…”
Section: Discussionmentioning
confidence: 99%
“…6,22 Moreover, experimental and epidemiological data have indicated that the inflammatory process is associated with impaired insulin sensitivity and the development of dysglycemic conditions. 30 A study conducted in Peru among 1525 individuals 31 found that elevated CRP were significantly and positively associated with increased mean fasting insulin concentrations and mean HOMA-IR (Po0.001) in both women and men. Women with CRP concentrations 42.53 mg l À1 (upper tertile) had a 2.18-fold increased risk of IR (OR¼2.18; 95% CI 1.51-3.16) compared with those in the lowest tertile (o0.81 mg l À1 ).…”
Section: Discussionmentioning
confidence: 99%
“…A PCR, proteína de fase aguda indicativa de inflamação sistêmica, tem sido considerada potente marcador de eventos cardiovasculares (RIDKER et al 2001; RIDKER e SILVERTON, 2007 (RIDKER et al, 1997, RIDKER e SILVERTON, 2007GELAYE et al, 2010).…”
Section: Considerações Iniciaisunclassified
“…RIDKER et al (1997) observaram risco três vezes maior de infarto do miocárdio em indivíduos sem histórico de DCV no quartil mais elevado de PCR quando comparados ao menor quartil. Também foram detectadas associações da PCR com glicemia, insulinemia e HOMA-IR, sugerindo que o metabolismo da glicose é afetado pela inflamação (RIDKER et al, 1997, RIDKER e SILVERTON, 2007GELAYE et al, 2010).…”
Section: Dcnts Associadas à Obesidadeunclassified
See 1 more Smart Citation
“…Elevated blood levels of CRP have been associated with atherosclerosis (Momiyama et al, 2010), unstable angina (Rizzello et al, 2007), diabetes (Shankar and Li, 2008), metabolic syndrome (Lai et al, 2010), insulin resistance (Gelaye et al, 2010), and obesity (Wee et al, 2008). Prospective studies have shown that increased blood CRP levels are associated with a greater risk of ischemic heart and cerebrovascular diseases (Sabatine et al, 2007;Oudi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%